Betacyanins functionalized selenium nanoparticles inhibit HepG2 cells growth via mitochondria-mediated pathway. (March 2021) - Tang, Xiang-Yi; Yu, Shu-Juan; Guo, Xiao-Ming; Li, He; Chen, Ming-Shun; Zhang, Tao; Lei, Cai-Yu; Zhao, Zhen-Gang; Meng, He-Cheng
Graphical abstract: Highlights: Six betacyanins were extracted and identified from red beetroot. XPS and FT-IR spectrum showed the presence of betacyanin on the surface of SeNPs. Betacyanin enhanced the stability and bioactivity of SeNPs. Bc@SeNPs-induced apoptosis in HepG2 cells was mediated through mitochondrial pathway. Abstract: Over the past few years, selenium nanoparticles (SeNPs)-mediated chemotherapy has aroused extensive attention for its low toxicity and high anti-tumor properties. However, the stability and anti-tumor properties of SeNPs require further improvement. In this study, betacyanin (Bc), a natural bioactive compound, was designed to decorate SeNPs with substantial anticancer efficacy. As revealed from the results, Bc-modified SeNPs (Bc@SeNPs) exhibited an average size of 133 nm and remained in a stable state for at least 1 month. Besides, the Bc@SeNPs exhibited a higher antioxidant activity and bioavailability compared with those of naked SeNPs. Moreover, Bc@SeNPs potentiated chemotherapy was demonstrated to exhibit superior in vitro anti-tumor efficacy against HepG2 hepatoma carcinoma cells, which could activate caspase cascade and induce mitochondria-mediated apoptosis. Overall, this study developed a novel strategy to increase the added value of red beet, and it was proved that Bc-functionalized SeNPs can act as potential chemotherapeutic agents for cancer therapy.